Empresas de segurança privada a bordo de navios - Medeiros, Maria Madruga de (2019)
The increase of piracy and armed robbery attacks has led to the growth of the hiring of private security companies (PSC) to protect ships, merchandise and crew. How-ever, the presence of armed guards on board ships gives rise to some legal prob-lems. The absence of a specific international treaty on PSCs that provide security on board ships, coupled with the fact that a ship may be in contact with various juris-dictions during its navigation raises questions about how States can regulate these companies and enforce the applicable international law. Thus, this dissertation aims to examine the international regulatory framework and to understand the interna-tional legal obligations applicable to States regarding the use of PSC in the mari-time environment. The delimitation of those obligations requires the analysis of the international binding (hard law) and non-binding (soft law) instruments relevant to this matter; a reflection on the adaptation of the Montreux Document definitions and obligations to the maritime context. Relevant international legal obligations of States can be found on this matter, although not as exhaustively as found in the Montreux Document.